Video-mediated dialogue for promoting equity in protected area conservation - Jayalaxshmi Mistry; Deirdre Jafferally; Sean Mendonca; Rebecca Xavier; Grace Albert; Bernie Robertson; Ena George; Ryan Benjamin; Lisa Ingwall-King (Oryx, 2023)
Improving equity in the context of protected areas conservation cannot be achieved in situations where people have different capabilities to participate. Participatory video has the potential to uncover hidden perspectives and worldviews and to build trustworthy, transparent and accountable relationships between marginalized communities and external agencies. We present findings from video-mediated dialogues between Indigenous peoples and decision makers involved in the management of three protected areas in Guyana. Participatory films created by Indigenous researchers in their communities were screened and discussed with protected area managers. We recorded their responses and presented them back to the communities. We show how the video-mediated process provided a rich and contextualized understanding of equity issues. It enabled recognition and respect by protected area managers for Indigenous lived experiences and the contribution of their values and knowledge. For Indigenous peoples, the participatory video process built confidence and critical reflection on their own activities and responsibilities whilst allowing them to challenge decision makers on issues of transparency, communication and accountability. We show that equity is an evolving process and that different protected areas with their differing histories and relationships with Indigenous communities produce distinct outcomes over time. Thus, promoting equity in protected areas and conservation must be a long-term process, enabling participation and producing the conditions for regular, transparent and honest communications. Standardized indicators of protected areas equity could be useful for reporting on international targets, but video-mediated dialogue can facilitate deeper understanding, greater representation and a recognition of rights.